GRFT – Genetic Records Family Tree Web Applet - Pimentel, Samuel; Fernandes, John; Walbot, Virginia (Frontiers in Genetics, 2011)
Current software for storing and displaying records of genetic crosses does not provide an easy way to determine the lineage of an individual. The genetic records family tree (GRFT) applet processes records of genetic crosses and allows researchers to quickly visualize lineages using a family tree construct and to access other information from these records using any Internet browser. Users select from three display features: 1) a family tree view which displays a color-coded family tree for an individual, 2) a sequential list of crosses, and 3) a list of crosses matching user-defined search criteria. Each feature contains options to specify the number of records shown and the latter two contain an option to filter results by the owner of the cross. The family tree feature is interactive, displaying a popup box with genetic information when the user mouses over an individual and allowing the user to draw a new tree by clicking on any individual in the current tree. The applet is written in Javascript and reads genetic records from a tab-delimited text file on the server, so it is cross-platform, can be accessed by anyone with an Internet connection, and supports almost instantaneous generation of new trees and table lists. Researchers can use the tool with their own genetic cross records for any sexually-reproducing organism. No additional software is required and with only minor modifications to the script, researchers can add their own custom columns. GRFT's speed, versatility, and low overhead make it an effective and innovative visualization method for genetic records. A sample tool is available at http://stanford.edu/ walbot/grft-sample.html.